A - Chilvers, Ian (Oxford University Press, 1998)
Providing broad coverage of painting, sculpture, drawing, and the applied arts, the dictionary has major entries on the important movements and styles of the twentieth century, including Dada, Cubism, Surrealism, Art Deco, Abstract Expressionism, Pop art, Body and Performance art, and Neo Expressionism. In addition there are entries on art schools and galleries, exhibitions and prizes, terms and techniques. The biographies feature not only artists but also collectors, critics, dealers, and patrons. And though the dictionary concentrates on the great names, it is not confined to the mainstream of modern art, featuring many artists working in a more popular tradition as well as interesting peripheral figures